MicroRNA-183-3p Is a Predictor of Worsening Heart Failure in Adult Patients With Transposition of the Great Arteries and a Systemic Right Ventricle - Abu-Halima, Masood; Meese, Eckart; Abdul-Khaliq, Hashim; Raedle-Hurst, Tanja (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT AIM: MicroRNAs (miRNAs) have been shown to play an important role in the progression of heart failure (HF). The aim of our study was to analyze miRNAs in the blood of patients with transposition of the great arteries and a systemic right ventricle (TGA-RV) in order to identify those that predict worsening HF. MATERIALS AND METHODS: In 36 patients with TGA-RV, SurePrint™ 8×60K Human v21 miRNA arrays were used to determine the miRNA abundance profiles and compared to 35 age- and gender-matched healthy volunteers (HVs). MiRNAs that were most significantly abundant or best related to worsening HF were further validated by RT-qPCR. RESULTS: Using miRNA array analysis, a total of 50 down-regulated and 56 up-regulated miRNAs were found to be differentially abundant in TGA-RV patients compared to HVs. 6 of these 106 miRNAs were significantly related to worsening HF. After validation by RT-qPCR, 4 miRNAs turned out to be significantly associated with worsening HF, namely miR-150-5p, miR-1255b-5p, miR-423-3p, and miR-183-3p. In the stepwise multivariable Cox regression analysis, ejection fraction of the systemic RV, high sensitive TNT and miR-183-3p were found to be independent predictors of worsening HF (P=0.001, P=0.002 and P=0.001, respectively). CONCLUSIONS: In patients with TGA-RV, miR-183-3p is an independent predictor of worsening HF and thus may be used as additional biomarker in the risk assessment of these patients.